Black Feminist Politics from Kennedy to Clinton. (Palgrave Macmillan, 2009)
Taking an interdisciplinary approach, this book analyzes Black women's involvement in American political life, focusing on what they did to gain political power between 1961 and 2001, and why, in many cases, they did not succeed.